Photocatalytic Conversion of Aminocyclopropanes to γ-Lactams by Sequential Ring-Expansion and Peripheral Diversification - Feng-Shuo Bao; Guo-Qing Li; Yu Qian; Ji-Chao Huang; Zhihan Zhang; Min Jiang; Jing Huang; Xiao-Ye Yu; Jia-Rong Chen; Wen-Jing Xiao (Journal of the American Chemical Society, 2026)
Abstract Rings underpin pharmaceuticals, agrochemicals, and materials, driving renewed interest in skeletal ring expansion. Current skeletal ring expansion strategies mainly focus on single-atom insertion or rearrangement; reliable methods for multiple single-atom insertion and peripheral diversification of saturated small rings are lacking. Herein, we report a general and efficient photocatalytic system directly converting aminocyclopropanes to γ-lactams via sequential C-/N-single-atom [n + 2] ring-expansion and peripheral diversification. The system accomplishes both γ-lactam formation and subsequent diversification at the γ-position via six distinct bond-forming reactions across hundreds of synthetic examples under predictable reaction conditions. Experimental and computational studies converge on photoredox-mediated radical pathways.